(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2021)
Introduction: Ackerman’s tumor or Verrucous carcinoma is a distinguished clinic-pathological variant of squamous cell carcinoma, presenting with multiple clinical presentations. This study provides a contemporary survey of morphological presentation of oral verrucous carcinoma (OVC) in the oral cavity with site of predilection and possible etiological factors. Method: An observational studywas conducted from January 2014 to June 2016.A suspected patient diagnosed clinically and histologically as OVC at the Dhaka Dental College Hospital (DDCH) was enrolled in this study. Results: In this study total 15 number of patients male were 53.3% and female were 47%. The morphological presentation of the study was proliferative and verrucous, each of which comprises 40.0% of cases. The tumor’s primary site was the buccal mucosa 46.67% and history ofbetel quid chewing was 46.9%. Conclusion: The study concluded that it is very difficult to distinguishing clinically between verrucous carcinoma and other exophytic lesions of the oral cavity. OVC presents with different morphological presentation such as proliferative and verrucous types. Buccal mucosa is the site of predilection. J Bangladesh Coll Phys Surg 2021; 39(2): 80-86